Bridging Entrepreneurship and Social Innovations. - Steurer, Elmar (Cambridge Scholars Publisher, 2021)
This book details how social innovations positively impact on non- or low-profit parts of society, such as education, health and energy, and describes a variety of methods for the successful implementation of entrepreneurship. The contributions here are based on the experience of authors from emerging countries, and present and explain practical advances in social innovation and transformative business management. Topics covered in this volume include additive manufacturing, the economic impact of such innovations on Japan's aging society, a multi-stakeholder analysis for business founders in.